School Counselor Suicide Response: A Final Rejoinder - Carrie A. Wachter Morris; Laura Gallo (Teaching and Supervision in Counseling, 2022)
In this article, we provide a summary of responses to Gallo and Wachter Morris (2022). We provide additional considerations based upon contributing authors’ perspectives and concluding thoughts on how to move forward on issues specific to school counselors’ roles in suicide prevention, assessment, and intervention in K-12 schools, as well as recommendations for pieces to consider for school counselor educators and practicing professional school counselors.
Keywords: School counseling; suicide assessment; professional identity; suicide risk assessment; suicide intervention; suicide prevention